Peningkatan Program Pengembangan Kewirausahaan (Ppk) Pengusaha Muda Fakultas Ilmu Keolahragaan Melalui Pembinaan, Pelatihan, dan Fasilitasi Menjadi Pengelola Sanggar Senam Aerobik, Senam Lansia dan Senam Hamil - Sri Gusti Handayani; Anton Komaini (Jurnal Berkarya Pengabdian Masyarakat, 2022)
The problems obtained from partners are; (a) There is no ability to do management in the management of a studio, so there is no fixed schedule for members who want to do gymnastics regularly, (b) there is no skill in Organizing and managing a gymnastics studio as a sustainable business (c) There is no trust high self-esteem for students who are members of the UK to lead gymnastics and studio management (d) There is no place for students to develop themselves as aerobic instructors, (e) Marketing or promotion is still minimal in the new normal era which only uses social media. The targets of this activity are the birth of a gymnastics studio with professional aerobics, elderly and pregnant gymnastics programs on campus, and the birth of 6 professional gymnastics instructors, as well as improving the management of small businesses related to fitness sports which will have an impact on increasing gymnastic members and increasing fitness for community groups. In addition, other outcomes after this service has been carried out are publications in national service journals with ISSN, videos that have been uploaded on YouTube, and reported in the mass media. The method that will be used in this service activity is through direct face-to-face training with lecture and demonstration methods at FIK UNP.